Benefits and limitations of e-textbook use - Lor, Chang (University of Wisconsin--Stout. Office of Research and Sponsored Programs, 2017)
E-textbooks are sometimes known as e-books, digital books, or online textbooks. E-textbooks are a growing alternative to printed textbooks at many academic institutions. At a university like the University of Wisconsin- Stout, where every student receives a laptop computer, it is important to examine how e-textbooks are accepted and how e-textbooks may affect the study habits of undergraduate students. The purpose of this research is to identify students’ preference for e-textbooks or analog, printed books, analyze the perception of student benefits and limitations of the medium, and investigate potential impacts of e-textbook use on the academic experience of UW-Stout undergraduate students.
Research article with graphs and tables.
Keywords: limitations; e-textbooks; benefits; academic; Electronic textbooks; Textbooks; University of Wisconsin--Stout--Students--Attitudes